Selected Topics in Facial Nerve Disorders - Al-Zwaini, Isam; Jalal Hussein, Mohammed (IntechOpen, 2019)
The facial nerve (seventh cranial nerve) is the nerve of facial expression. It innervates all superficial muscles of the face and scalp, the contraction of which is responsible for all our numerous facial expressions like anger, pain, fear, smile, etc. Facial disfigurement resulting from facial nerve disorders can affect the physical, psychological, and emotional integrity of an individual. This might result in a social, occupational, and educational handicap. The facial nerve is one of the most common cranial nerves implicated by disorders. Common disorders involving the facial nerve include Bell's palsy, tumors, hemifacial spasm, and blepharospasm. Among these disorders, Bell's palsy is the commonest with an annual global incidence of 11.5-53.3 per 100,000 in different populations, and it accounts for approximately 60-75% of cases of acute unilateral facial paralysis with the right side being affected in 63% of cases.